2021
DOI: 10.4314/gjpas.v27i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of boko haram insurgency on the nutritional status of two communities in Gulani Local Government Area, Yobe State, Nigeria

Abstract: The Boko Haram insurgency has consistently posed a threat to the lives of residents in the North-East and national security in general. The insurgency has led to increased incidence of diseases, food insecurity, unemployment, violation of human rights, displacements and shelter problems among others. The study was designed to investigate the impact of boko haram insurgency on the nutritional status of two communities in Gulani Local Government Area, Yobe State, Nigeria. The study was a descriptive cross sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition to these challenges, Boko Haram insurgency in the Northeast poses even greater challenge to rural farmers. This was evident in a descriptive cross-sectional survey (Musab and Otovwe, 2021).…”
Section: Impacts Of Boko Haram Insurgency On Food Security and Malnut...mentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to these challenges, Boko Haram insurgency in the Northeast poses even greater challenge to rural farmers. This was evident in a descriptive cross-sectional survey (Musab and Otovwe, 2021).…”
Section: Impacts Of Boko Haram Insurgency On Food Security and Malnut...mentioning
confidence: 87%
“…The survey which was conducted among 391 respondents showed that, Boko Haram insurgency in the zone (Northeast) continues to pose serious challenge on food production. This has led to increase of food prices and poor nutritional status among the residents from the affected areas (Musab and Otovwe, 2021). Millions of persons have been displaced in their place of domicile where farming activities was not threatened (Ilesanmi and Odefadehan, 2022), leading to a decrease in food production in the Northeast, with impacts being felt across the country.…”
Section: Impacts Of Boko Haram Insurgency On Food Security and Malnut...mentioning
confidence: 99%